2011
DOI: 10.1038/cr.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of size control in development and human diseases

Abstract: How multicellular organisms control their size is a fundamental question that fascinated generations of biologists. In the past 10 years, tremendous progress has been made toward our understanding of the molecular mechanism underlying size control. Original studies from Drosophila showed that in addition to extrinsic nutritional and hormonal cues, intrinsic mechanisms also play important roles in the control of organ size during development. Several novel signaling pathways such as insulin and Hippo-LATS signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 176 publications
(196 reference statements)
1
58
0
Order By: Relevance
“…If Hippo signaling is only involved in inhibiting cell division, loss of Hippo signaling would result in extra cells that are smaller than normal cells. By altering activities of some cell-cycle regulators, it has been previously shown that an increase of cell division rate was insufficient to drive cellular growth, and therefore, cell division and cellular growth can be separately regulated (reviewed by Yang and Xu, 2011). In the case of Hippo signaling, this growthinhibitory pathway appears to play an active role to negatively control both cell division and cellular growth.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…If Hippo signaling is only involved in inhibiting cell division, loss of Hippo signaling would result in extra cells that are smaller than normal cells. By altering activities of some cell-cycle regulators, it has been previously shown that an increase of cell division rate was insufficient to drive cellular growth, and therefore, cell division and cellular growth can be separately regulated (reviewed by Yang and Xu, 2011). In the case of Hippo signaling, this growthinhibitory pathway appears to play an active role to negatively control both cell division and cellular growth.…”
Section: Discussionmentioning
confidence: 96%
“…en-Galt4 drives expression of UAS transgenes in the P compartment. Hietakangas and Cohen, 2009;Yang and Xu, 2011). The observation that tumor cells generated by losing Hippo signaling activity are similar in size compared to normal cells (e.g.…”
Section: Genetic Interaction Between Akt and Mats In Regulating Cell mentioning
confidence: 96%
“…This is reflective of the robust nature of the developmental process in the face of inevitable variations at all levels, ranging from molecular to organismal and environmental levels (Patel and Lall, 2002;Flatt, 2005;Martinez Arias and Hayward, 2006;Hendrikse et al, 2007;Lander, 2007;Lott et al, 2007). A full, mechanistic understanding of scaling requires knowledge about two distinct aspects of development: specification of scaled patterns and coordinated tissue growth (Su and O'Farrell, 1998;Day and Lawrence, 2000;Crickmore and Mann, 2008;BenZvi et al, 2011;Wartlick et al, 2011;Yang and Xu, 2011;BaenaLopez et al, 2012). Recent quantitative studies have uncovered insights into scaled patterning specification in Drosophila (Houchmandzadeh et al, 2002;Gregor et al, 2005;He et al, 2008;Manu et al, 2009;Cheung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, excessive insulin signaling caused by hyperinsulinemia or overexpression of insulin receptor (IR) has been linked to cancer progression. 5 Recent epidemiological and experimental studies have demonstrated that hyperinsulinemia is a major cancer risk factor among many type 2 diabetes mellitus patients and obese individuals.…”
Section: Introductionmentioning
confidence: 99%